2019
DOI: 10.3389/fgene.2019.00764
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of One Carbon Metabolism on Histone Methylation

Abstract: The effect of one carbon metabolism on DNA methylation has been well described, bridging nutrition, metabolism, and epigenetics. This modification is mediated by the metabolite S-adenosyl methionine (SAM), which is also the methyl-donating substrate of histone methyltransferases. Therefore, SAM levels that are influenced by several nutrients, enzymes, and metabolic cofactors also have a potential impact on histone methylation. Although this modification plays a major role in chromatin accessibility and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 70 publications
2
65
0
1
Order By: Relevance
“…Perhaps folate's role in altering the hippocampal expression landscape can be partially explained by post-translational modification of MafB and Zfp410 or by altered methylation status in their binding regions. This is consistent not only with folate's pivotal role in DNA methylation, but also with the implications of folate deficiency on post-translational modification of various proteins including histones, septins regulating neural tube closure, and endothelial nitric oxide synthase in cardiovascular disease (76)(77)(78).…”
Section: Discussionsupporting
confidence: 80%
“…Perhaps folate's role in altering the hippocampal expression landscape can be partially explained by post-translational modification of MafB and Zfp410 or by altered methylation status in their binding regions. This is consistent not only with folate's pivotal role in DNA methylation, but also with the implications of folate deficiency on post-translational modification of various proteins including histones, septins regulating neural tube closure, and endothelial nitric oxide synthase in cardiovascular disease (76)(77)(78).…”
Section: Discussionsupporting
confidence: 80%
“…Acetylation on the N-terminal lysine tail of histones facilitates an open chromatin configuration to promote gene expression, using intermediary metabolite acetyl-CoA as the co-substrate for modification [85]. In addition to DNA methylation, histone methylation is also important in defining the epigenetic status of the cells [85], and the methyl-donor S-adenosylmethionine (SAM) is utilized by methyltransferases for both DNA and histone methylation [71]. In EGFR-mutant GBMs which do not usually possess mutations in IDH or the H3 histone family 3A (e.g.…”
Section: Egfr-mtor Pathways: a Key Player In Modulating Glioma Histonmentioning
confidence: 99%
“…Some nutrients are used as a substrate for one-carbon metabolic pathway, making methylation highly dependent on their availability. Methionine, for example, is the precursor of SAM and a key nutritional factor limiting its synthesis (Serefidou et al, 2019). Thus, fluctuations of methionine can influence DNA methylation and gene expression.…”
Section: Metabolic Regulation Of Dna/histone Methylation and Demethylmentioning
confidence: 99%
“…Still in this context, the factors involved in one carbon metabolism also act as critical cofactors or inhibitors of histone modifiers, making the histone methylation status also tightly connected to the cells' metabolic state (Serefidou et al, 2019). Recent studies demonstrated that the reduction of SAM induced by defects in methionine metabolism alter the dynamics of histone methylation.…”
Section: Metabolic Regulation Of Dna/histone Methylation and Demethylmentioning
confidence: 99%